What is known about the patient's experience of medical tourism? A scoping review - Crooks Valorie A; Kingsbury Paul; Snyder Jeremy; Johnston Rory (BMC, 2010)
Abstract Background Medical tourism is understood as travel abroad with the intention of obtaining non-emergency medical services. This practice is the subject of increasing interest, but little is known about its scope. Methods A comprehensive scoping review of published academic articles, media sources, and grey literature reports was performed to answer the question: what is known about the patient's experience of medical tourism? The review was accomplished in three steps: (1) identifying the question and relevant literature; (2) selecting the literature; (3) charting, collating, and summarizing the information. Overall themes were identified from this process. Results 291 sources were identified for review from the databases searched, the majority of which were media pieces (n = 176). A further 57 sources were included for review after hand searching reference lists. Of the 348 sources that were gathered, 216 were ultimately included in this scoping review. Only a small minority of sources reported on empirical studies that involved the collection of primary data (n = 5). The four themes identified via the review were: (1) decision-making (e.g., push and pull factors that operate to shape patients' decisions); (2) motivations (e.g., procedure-, cost-, and travel-based factors motivating patients to seek care abroad); (3) risks (e.g., health and travel risks); and (4) first-hand accounts (e.g., patients' experiential accounts of having gone abroad for medical care). These themes represent the most discussed issues about the patient's experience of medical tourism in the English-language academic, media, and grey literatures. Conclusions This review demonstrates the need for additional research on numerous issues, including: (1) understanding how multiple information sources are consulted and evaluated by patients before deciding upon medical tourism; (2) examining how patients understand the risks of care abroad; (3) gathering patients' prospective and retrospective accounts; and (4) the push and pull factors, as well as the motives of patients to participate in medical tourism. The findings from this scoping review and the knowledge gaps it uncovered also demonstrate that there is great potential for new contributions to our understanding of the patient's experience of medical tourism.